2021
DOI: 10.3389/fimmu.2021.631869
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Does Not Increase the Risk of Cardiac Arrhythmia in Common Rheumatic Diseases: A Nationwide Population-Based Cohort Study

Abstract: ObjectivesHydroxychloroquine (HCQ) is widely used to treat rheumatic diseases including rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and Sjögren’s syndrome (SS). Cardiac arrhythmia has been concerned as important safety issue for HCQ. The aim of this study was to investigate whether hydroxychloroquine increases new-onset arrhythmia among patients with RA, SLE or SS.MethodsThis was a retrospective cohort study that conducted from the longitudinal health insurance database of Taiwan. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Our results suggest potential antiarrhythmic effects of HCQ against AF. Other studies have shown that HCQ treatments did not significantly increase the risk of cardiac arrhythmias, including ventricular arrhythmias, in patients with SLE [ 40 , 41 ] and common rheumatic diseases [ 42 ]. Although some case reports showed that HCQ could lead to QT prolongation [ 13 , 43 ], HCQ use was not associated with QTc length in a large cohort of patients with rheumatic diseases [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest potential antiarrhythmic effects of HCQ against AF. Other studies have shown that HCQ treatments did not significantly increase the risk of cardiac arrhythmias, including ventricular arrhythmias, in patients with SLE [ 40 , 41 ] and common rheumatic diseases [ 42 ]. Although some case reports showed that HCQ could lead to QT prolongation [ 13 , 43 ], HCQ use was not associated with QTc length in a large cohort of patients with rheumatic diseases [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results imply the potential antiarrhythmic effects of HCQ against AF. Other studies have shown that HCQ treatments did not significantly increase the risk of cardiac arrhythmias, including ventricular arrhythmias, in patients with SLE [40, 41] and common rheumatic diseases [42]. Although some case reports showed that HCQ could lead to QT prolongation [13, 43], HCQ use was not associated with QTc length in a large cohort of patients with rheumatic diseases [44].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding the use of hydroxychloroquine (HCQ), one of the most used drugs in SS, and cardiac arrhythmia have been based on the fact that HCQ can prolong the QT interval. However, in a recent ample study, it was shown that HCQ did not increase the risk of ventricular arrhythmia (regardless of cumulative dose or duration of treatment) in patients with various autoimmune diseases, including SS ( 111 ). The role of the ECG-based screening for the detection of LQTS in patients with SS is not clear.…”
Section: Cardiovascular Involvement In Sjogren’s Syndromementioning
confidence: 97%